2016
DOI: 10.1186/s12916-016-0672-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of mitochondrial inhibitory factor 1 are independently associated with long-term prognosis in coronary artery disease: the GENES Study

Abstract: BackgroundEpidemiological and observational studies have established that high-density lipoprotein cholesterol (HDL-C) is an independent negative cardiovascular risk factor. However, simple measurement of HDL-C levels is no longer sufficient for cardiovascular risk assessment. Therefore, there is a critical need for novel non-invasive biomarkers that would display prognostic superiority over HDL-C. Cell surface ecto-F1-ATPase contributes to several athero-protective properties of HDL, including reverse cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Consistent with these findings, it has been reported that IF1-knockout mice are protected from pressure overload-induced cardiac hypertrophy (37). In the same line, the plasma levels of IF1 have been claimed to provide a biomarker for the risk of experiencing cardiovascular disease (30). Whereas no differences were found in the tissue expression level of IF1 in mice from different genetic backgrounds, a dissimilar expression pattern of IF1 was observed between some human and mouse tissues.…”
Section: Discussionmentioning
confidence: 55%
“…Consistent with these findings, it has been reported that IF1-knockout mice are protected from pressure overload-induced cardiac hypertrophy (37). In the same line, the plasma levels of IF1 have been claimed to provide a biomarker for the risk of experiencing cardiovascular disease (30). Whereas no differences were found in the tissue expression level of IF1 in mice from different genetic backgrounds, a dissimilar expression pattern of IF1 was observed between some human and mouse tissues.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, despite a plethora of imaging techniques and biomarkers, CAD is still primarily diagnosed and managed symptomatically (93) . Recent advances in characterizing CAD gene networks 94 , 95 could be coupled with advanced imaging 96 , 97 and a wide variety of novel biomarkers 98 , 99 , 100 , 101 , 102 , 103 , 104 to stratify patients with this heterogeneous disease and make more informed treatment decisions.…”
Section: Examples Of Cardiovascular Diseases Amenable To Precision Sumentioning
confidence: 99%
“…Moreover, in clinical studies, circulating IF1 was found to be an independent determinant of HDL-Cholesterol (HDL-C) levels and its mean concentration was lower in coronary heart disease (CHD) patients than in paired control individuals (430 ng/mL and 530 ng/mL, respectively; p <0.001). Later, IF1 levels were found to independently and negatively associate with mortality in CHD patients [35]. Recently, higher levels of circulating IF1 were also reported to be significantly associated with greater muscle mass [6].…”
Section: Introductionmentioning
confidence: 99%